Factors Affecting Corporate Governance and Its Implication on Accounting Information Quality: Indonesia Trusted Company Awardees - Judith Gallena Sinaga; Hamfri Djajadikerta; Amelia Setiawan (Faculty of Business, President University, 2022)
This study aims to explain the factors affecting corporate governance and its implication on accounting information quality. Globally, there are many companies that collapsed due to misleading accounting information. Companies declares financial statements as free from errors or misstatements wherein fact it misleads financial statements users. There were 36 firm year observation being analyzed using PLS-SEM to process the available data. The results showed that audit committee and board of directors have significant effect on good corporate governance, while institutional ownership has no significant effect on good corporate governance. On the other hand, corporate governance has significant effect on accounting information quality. This is an indication that the quality of accounting information depends on the practice of good corporate governance. Strict compliance of rules and regulations lead to better governance of publicly listed companies. The originality of this research is that this is the first ever study that had focused on the awardees for mostly trusted, trusted, and fairly trusted companies listed in Indonesia Stock Exchange.